Impact of the tariff variation of the Value Added Tax on spending in Ecuador - Parra Gavilanes , Daniel Alberto (2022)
The current economic-financial situation of Ecuador reinforces the social need that higher education, through the methodological-investigative tools and the academic proposal, intervenes in the national debate. The study problem is the rate variation of the Value Added Tax (VAT) and its impact on the behavior of expenditure in Ecuador. The object of study is the tax collection of the fiscal periods 2015-2018, taking into account that in this period the 14% tariff was applied (except Manabí and Esmeraldas) to cover the reconstruction of the populations affected by the earthquake of April of the 2016. The research objective is to project the impact of a VAT rate variation on spending in Ecuador. The theoretical contribution allows us to know the fiscal experiences of other Latin American nations, as well as the opinions of professionals in the field at the national level. The methodological contribution is supported by the application of econometric models and the relationship between tax collection and consumption expenditure. The practical contribution is to present prediction models that allow contributing to the debate of the current national situation, on the treatment of VAT as a tool to cover the fiscal needs and at the same time allow the efficient growth of the Ecuadorian economy.